Sin3a associated protein 130 kDa, sap130, plays an evolutionary conserved role in zebrafish heart development - DeMoya, Ricardo A.; Forman-Rubinsky, Rachel E.; Fontaine, Deon; Shin, Joseph; Watkins, Simon C.; Lo, Cecilia W.; Tsang, Michael (Frontiers in Cell and Developmental Biology, 2023)
Hypoplastic left heart syndrome (HLHS) is a congenital heart disease where the left ventricle is reduced in size. A forward genetic screen in mice identified SIN3A associated protein 130 kDa (Sap130), part of the chromatin modifying SIN3A/HDAC complex, as a gene contributing to the etiology of HLHS. Here, we report the role of zebrafish sap130 genes in heart development. Loss of sap130a, one of two Sap130 orthologs, resulted in smaller ventricle size, a phenotype reminiscent to the hypoplastic left ventricle in mice. While cardiac progenitors were normal during somitogenesis, diminution of the ventricle size suggest the Second Heart Field (SHF) was the source of the defect. To explore the role of sap130a in gene regulation, transcriptome profiling was performed after the heart tube formation to identify candidate pathways and genes responsible for the small ventricle phenotype. Genes involved in cardiac differentiation and cardiac function were dysregulated in sap130a, but not in sap130b mutants. Confocal light sheet analysis measured deficits in cardiac output in MZsap130a supporting the notion that cardiomyocyte maturation was disrupted. Lineage tracing experiments revealed a significant reduction of SHF cells in the ventricle that resulted in increased outflow tract size. These data suggest that sap130a is involved in cardiogenesis via regulating the accretion of SHF cells to the growing ventricle and in their subsequent maturation for cardiac function. Further, genetic studies revealed an interaction between hdac1 and sap130a, in the incidence of small ventricles. These studies highlight the conserved role of Sap130a and Hdac1 in zebrafish cardiogenesis.